The Brain of Tomorrow, Google, and Creativity. - Naccache, Lionel; Naccache, Karine (Contemporary French & Francophone Studies, 2019)
In the article, the author discusses how the human brain can adapt to technological innovations like the Internet, social media, artificial intelligence, and virtual reality. Also cited are the 2011 study by psychologist Betsy Sparrow on the functioning of the brain, the cognitive interiorization of the search engines, and the machine-brain interfaces.